Effect of BCG vaccination against pulmonary tuberculosis in the rural population, Thailand - Natsir, Rostiaty
BCG vaccination has been used worldwide for more than 60 years. Several studies had been conducted to determine its protective effect. The results were contradictory. A case control study was conducted among rural population in Regional TB Center 2 Saraburi province to assess the effect of BCG vaccination against pulmonary tuberculosis. Cases and controls were chosen from all patients who consulted for the first time at this center from October 1993 to May 1994. Out of 646 patients interviewed, only 389 satisfied the rural residence criterion. A diagnosis of pulmonary tuberculosis was based on clinical symptomatology and positive smear. There were 78 cases and for each case, 2 controls were selected from the file of potential controls interviewed. This study failed to demonstrate the protective effect of BCG vaccination. Several factors might contribute for the non-significant protection of the vaccine such as: the vaccine storage (inadequate maintenance of cold chain) and its administration in the field (ineffective vaccination technique).